Recommendations for the Design and Construction of Reinforced Concrete Strip Road Pavements (2018)
The construction of reinforced concrete strip road pavements has increased in Colombia in recent years. The vast majority of the projects are based on the 500-1P specification, which presents a general design, of which the criteria taken into account in its elaboration are unknown, which generates many doubts for its use in different projects. In the present article, an analysis of strip road pavement is made and recommendations are given for the design and construction of this type of pavement, taking into account current conditions of use, expected loads, characteristics of the supporting soil, and qualities of materials.